Statistical analysis of load demand distribution at Banaras Hindu University, India - Kumar M.; Samuel C. (My University, 2025)
There are various segments of energy sources like coal, oil, gas and renewable energy to generate electricity. Owing to the reason of being carbon free energy sources, utilization of renewable energy resources are increasing exponentially. It is clear from the recent past, role of renewable distributed generation technologies are the most demanded one. Optimal utilization of renewable energy sources and continuous electricity supply at any location needs statistical analysis to predict the randomly distributed electricity load demand of same location. For the statistical analysis, we have collected hourly load demand data of Banaras Hindu University (BHU), India region for the year 2014 from the Electricity & Water Supply Service (EWSS) centre, BHU. In this research work, we have considered Lognormal, Weibull and Rayleigh probability distributions to estimate the randomly distributed load demand data of BHU region. We had taken help of STATISTICA software for the statistical analysis and comparative study between these three probability distributions. With the help of Kolmogorov-Smirnov, Anderson-Darling and Chi-Square Goodness-of-fit tests, we identified that Lognormal distribution is the best fitted one. © 2016 IEEE.